2019
DOI: 10.1002/pds.4907
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of metformin versus insulin for gestational diabetes in New Zealand

Abstract: Purpose To measure the comparative effectiveness of metformin versus insulin for initial pharmacological management of gestational diabetes mellitus (GDM). Methods We conducted a population‐based retrospective cohort study using administrative claims, maternity care, and laboratory result data from New Zealand. We followed pregnant women aged 15 to 45 from GDM diagnosis through delivery and assessed outcomes using maternity care and hospitalization data. We adjusted for covariates using inverse probability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
9
1
1
Order By: Relevance
“…One RCT found that newborn birth weight of the metformin group was lower compared to the insulin group, indicating that metformin could reduce the newborn birth weight to some degree (77). In addition, we found that several meta-analyses showed that metformin reduced birth weights of newborns compared with insulin (45,66,67); however, a recent retrospective cohort study showed no clinically significant difference in neonatal mean birth weight between pregnant women treated with metformin and insulin (63). Another RCT showed no statistically significant difference in the average birth weight between metformin and insulin treatment groups (54).…”
Section: Neonatal Intensive Care Unit (Nicu) Occupancy Ratementioning
confidence: 66%
See 2 more Smart Citations
“…One RCT found that newborn birth weight of the metformin group was lower compared to the insulin group, indicating that metformin could reduce the newborn birth weight to some degree (77). In addition, we found that several meta-analyses showed that metformin reduced birth weights of newborns compared with insulin (45,66,67); however, a recent retrospective cohort study showed no clinically significant difference in neonatal mean birth weight between pregnant women treated with metformin and insulin (63). Another RCT showed no statistically significant difference in the average birth weight between metformin and insulin treatment groups (54).…”
Section: Neonatal Intensive Care Unit (Nicu) Occupancy Ratementioning
confidence: 66%
“…Therefore, to further understand the therapeutic effect of metformin on GDM, we summarized some studies on the control of blood glucose by metformin in pregnant women with GDM to further explore the effect of metformin on blood glucose in GDM in Table 1 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). At the same time, we also summarized the randomized controlled trials (36-37, 39-41,52-57), observational studies (43,(58)(59)(60)(61)(62)(63) and metaanalyses (34,(44)(45)(46)(47)(48)(49)(50)(51)(64)(65)(66)(67)(68)(69) of the effects of metformin on maternal and infant outcomes of pregnant women with GDM, and discussed the effects of metformin on maternal and infant outcomes in GDM in Table 2.…”
Section: Efficacy Evaluation Of Metformin In the Treatment Of Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Es scheint daher naheliegend, dass -zumindest in Bezug auf die Adipositas des Kindes -eine Lifestyle-Modifikation mit präkonzeptionellem Gewichtsverlust durch Ernährungsumstellung und körperliche Betätigung nicht nur der Mutter, sondern auch dem Kindsvater empfohlen werden sollte [21]. [23,24].…”
Section: Lifestyle-modifikationunclassified
“…Due to its ability to cross the placenta and limited long-term safety data on offspring, clinical use of metformin in the treatment of gestational has been concerned [10,11]. However, there is accumulating evidence both in animals and humans indicated that metformin is an effective and safe option for the treatment of diabetes during pregnancy and breastfeeding, providing some metabolic benefits on offspring compared to insulin without adverse effects on long-term growth and development [12,13]. However, most of these animal studies investigated the effects of maternal metformin exposure throughout both gestation and lactation periods or just focusing on the gestation period.…”
Section: Introductionmentioning
confidence: 99%